When Jesus Rose Early: Studies on the Text and Paratexts of Mark's Ending - Monier, Mina, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
When Jesus Rose Early is the first comprehensive study of the Markan conclusion to utilise the full potential of the digital revolution in manuscript research. You'll explore how scribes addressed the Gospel's ending through centuries, forging vital new textual traditions. With new manuscript evidence, this book reveals how manuscript marginalia, paratextual notes, and catena commentaries challenge conventional models and even modern categories like "endings". Unpublished data from ancient manuscripts in a spectrum of languages unlocks fresh perspectives on early Christian thought. By merging groundbreaking research with a multidisciplinary approach, this work enriches New Testament Textual Criticism, biblical studies, and patristics.